Fans' perceptions towards video assistant referee (VAR) in the English Premier League - Tommy Hamsund; Nicolas Scelles (Journal of Risk and Financial Management, 2021)
The video assistant referee (VAR) in association football was developed to help on-field referees judge potentially game-changing decisions correctly by reviewing video evidence in real time. VAR was implemented by the English Premier League (EPL) ahead of the 2019/20 season. Despite its potential benefits, VAR also presents the risk of not being well perceived by fans. This article aims to investigate fans' perceptions towards VAR in the EPL. Total of 1350 EPL fans from different age groups above 18 years old completed an online survey on their opinion of VAR and changes they felt would make VAR better. The majority of fans were happy for VAR to continue being used in the EPL, but expressed that changes need to be made in terms of how VAR is being used by on-field referees and to assess certain situations. All age groups were generally positive towards the idea of using technology in the EPL to support referee decisions and provide more information to in-stadium fans, but younger age groups showed significantly more positive perceptions than their older counterparts. Implications include advice for the EPL to make changes according to fans' opinions and to develop frameworks for making changes with fans as stakeholders in mind.
Keywords: 330; video assistant referee (VAR); fans’ perceptions; English Premier League; changes; age groups